2013
DOI: 10.1038/ja.2012.120
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and biosynthesis of C-demethylactinomycins in actinomycin-producing Streptomyces chrysomallus and Streptomyces parvulus

Abstract: Streptomyces chrysomallus and Streptomyces parvulus produce novel C-demethylactinomycins besides their normal actinomycins when fed with 3-hydroxyanthranilic acid (3-HA). The 3-HA is incorporated into pentapeptide lactone precursors in competition with the regular precursor 4-methyl-3-hydroxyanthranilic acid (4-MHA). The resultant 3-HA pentapeptide lactones can condense with each other, as well as with the continuously formed 4-MHA pentapeptide lactones giving C-demethylactinomycins lacking one or both methyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…It was recently reported that 70 % of all antibiotics in use were derived from actinomycetes bacteria [2], 75 % of these from the genus Streptomyces [4][5][6]. Antibiotics derived from Streptomyces have antibacterial, antifungal, antioxidant, and antitumor activities [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that 70 % of all antibiotics in use were derived from actinomycetes bacteria [2], 75 % of these from the genus Streptomyces [4][5][6]. Antibiotics derived from Streptomyces have antibacterial, antifungal, antioxidant, and antitumor activities [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Natural actinomycins differ in amino acid composition of the peptidolactone side chains, whereas the chromophore (2-amino-4,6-dimethylphenoxazine-3-one-1,9-dicarboxylic acid, actinocin) is identical in all reported actinomycins 2 . Recently, S. chrysomallus and S. parvulus were reported to generate new C-demethylactinomycins lacking one or both methyl groups in their phenoxazinone chromophores when cultured with 3-hydroxyanthranilic acid 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The calculated mass of actinomycin was 1255.42 Da. The major peak detected in plasma samples was sodium adduct of ActD [M + Na] + , which exhibits a mass peak at m/z 1277.25 (Crnovcic et al, 2013).…”
Section: Maldi Mass Spectrometry Of Plasmamentioning
confidence: 99%